A study on the behavioral performance of LIS paraprofessionals in delivering reference services in Quezon City Public Library branches - Valdez, Jonathan A. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
Since the beginning of modern libraries, reference service is regarded as one of the most important library functions as it directly addresses the information needs of the library clientele. However, this library work is delegated to LIS paraprofessionals or non-licensed library workers, whose lack of LIS academic and professional background might jeopardize the quality of reference service the public library delivers. Yet because of the lack of qualified staff, public libraries in Metro Manila are dominated by LIS paraprofessionals.